Manajemen Sekolah dalam Menghadapi Revolusi Industri 4.0 di Masa Pandemi - Edi Sugianto (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2021)
This study is intended to find data about the management of SMA Muhammadiyah 3 Jakarta (MUGA) in the face of the Industrial Revolution / RI 4.0, and their learning strategies during the pandemic. This research is qualitative research, researchers collect data through interviews, observation and documentation. Then, analyze using the Miles and Huberman model, which summarizes, presents, and concludes the data. This research concludes that MUGA is a school that is always ready to face any era and in any situation.Keywords : School Management, Educational Stakeholders, and Industrial Revolution 4.0.